2021
DOI: 10.1128/cmr.00228-20
|View full text |Cite
|
Sign up to set email alerts
|

Tools and Techniques for Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2)/COVID-19 Detection

Abstract: SUMMARY The coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory disease coronavirus 2 (SARS-CoV-2), has led to millions of confirmed cases and deaths worldwide. Efficient diagnostic tools are in high demand, as rapid and large-scale testing plays a pivotal role in patient management and decelerating disease spread. This paper reviews current technologies used to detect SARS-CoV-2 in clinical laboratories as well as advances made for molecular, antigen-based, and immunological point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
232
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(280 citation statements)
references
References 571 publications
(815 reference statements)
3
232
0
4
Order By: Relevance
“…False positive and negative results occur with any diagnostic test, but are increasingly likely when manufacturer recommendations are not followed. [1,14,15] Using the Panbio SARS-CoV-2 Ag-RDT, this study demonstrated test conditions outside manufacturer recommendations that can cause false positive results. In absence of manufacturer buffer, a variety of food, water, laboratory buffer, specimen transport media, and clinical specimens showed false positive reactions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…False positive and negative results occur with any diagnostic test, but are increasingly likely when manufacturer recommendations are not followed. [1,14,15] Using the Panbio SARS-CoV-2 Ag-RDT, this study demonstrated test conditions outside manufacturer recommendations that can cause false positive results. In absence of manufacturer buffer, a variety of food, water, laboratory buffer, specimen transport media, and clinical specimens showed false positive reactions.…”
Section: Discussionmentioning
confidence: 94%
“…High demand for diagnostic testing during the COVID-19 pandemic led to the development of various technologies for SARS-CoV-2 detection. [1] Nucleic acid amplification tests (NAATs), like real-time RT-PCR, are considered the reference methods [1][2][3], but antigen-based rapid diagnostic tests (Ag-RDTs) have been widely used due to their ease-of use, rapid results, and ability to be performed outside of a laboratory setting. [1] Many Ag-RDTs have been licensed as point-of-care (POC) devices for SARS-CoV-2 detection [4,5], but their performance can vary between methods, testing frequency, and settings in which they are used.…”
Section: Introductionmentioning
confidence: 99%
“…Reprinted with permission from ref. [ 8 ]. Copyright 2021 American Society for Microbiology-Journals.…”
Section: Figurementioning
confidence: 99%
“…Several nucleic acid detection tests targeting N, E, S, or RNA-dependent RNA polymerase genes of the virus are commercially available for the diagnosis of COVID-19. 7 9 Viral RNA detection by quantitative reverse transcription polymerase chain reaction (RT-qPCR) is currently the gold standard test for SARS-CoV-2 infection. 10 , 11 Although this nucleic acid amplification test is highly sensitive with the limit of detection as low as 1 RNA copy/μL, RT-PCR needs expensive laboratory instrument, skilled technicians, and days to get the result.…”
Section: Introductionmentioning
confidence: 99%